Notes on the book of Isaiah ; v. 2 critical, explanatory and practical with a new translation and an introductory dissertation - Barnes, Albert; Cumming, John (London, UK Gall and Inglis)
Contents : v. 2 : Isaiah 36-66
Keywords: Bible. O.T. Isaiah XXXVI-LXVI -- commentaries